Effects of increasing physical load and fatigue on the biomechanics of elite cyclists - Bartaguiz, E.; Dindorf, C.; Dully, J.; Becker, S.; Fröhlich, M. (Scientific Journal of Sport and Performance, 2023)
In this study, we propose to expand the research on the biomechanics of cycling, including changes caused by riding at different intensity levels and fatigue, similar to training or competition. Six well-trained, experienced male road cyclists (27.17 ± 3.89 years; 180.41 ± 5.31 cm; 75.23 ± 4.91 kg) with 8.3 ± 4.85 years of (professional) experience in road cycling underwent a lactate test, starting with 100 W and an increment of 20 W every 3 minutes until total exhaustion. Afterward, subjects drove an increment of 50 W every 3 minutes, starting again with 100 W and ending with 250 W (post-test). Changes in position were recorded via 2D video analysis. We found that with higher power output relative to the individual anaerobic threshold (IAT), the joint angles changed. No significant differences were present for the pre-post comparisons of the examined angles, which should map the influence of fatigue (p > .05). Future research should try to observe cycling movement in more realistic settings, such as cycling-specific fatigue or during an outdoor ride, as the biomechanics under these conditions are of particularly high relevance for the athletes. Overall, the results suggest performing bike fitting more individually and in more realistic situations or setting.